Assistance for Poor Empowerment through the Village Economic Business Program - Saving and Loan ( UED-SP) - Yanto Irianto; Andita Hadi (Asian Journal of Community Services, 2022)
The purpose of this study was to find out and analyze the implementation of the empowerment of the poor through the UED-SP Program in Cempaka, Plumbon District, Cirebon Regency. The research method uses a survey approach that is descriptive in nature, namely research that seeks to describe existing problem solving that is supplemented by existing literature. Data collection techniques were used in this study in three ways, namely interviews, written sources (documentation), supplemented by questionnaires. The results of the study showed that the performance of the UED-SP Program managers was assessed by the community, especially program recipients, as being considered good.